2020
DOI: 10.1109/tmi.2020.2974574
|View full text |Cite
|
Sign up to set email alerts
|

MS-Net: Multi-Site Network for Improving Prostate Segmentation With Heterogeneous MRI Data

Abstract: Automated prostate segmentation in MRI is highly demanded for computer-assisted diagnosis. Recently, a variety of deep learning methods have achieved remarkable progress in this task, usually relying on large amounts of training data. Due to the nature of scarcity for medical images, it is important to effectively aggregate data from multiple sites for robust model training, to alleviate the insufficiency of single-site samples. However, the prostate MRIs from different sites present heterogeneity due to the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
162
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 236 publications
(163 citation statements)
references
References 46 publications
1
162
0
Order By: Relevance
“…In knowledge transfer task (Task 3), simply fusing non-COVID-19 and COVID-19 dataset with the SOTA network could bias the model to learn more non-COVID-19 features. One can use more robust and powerful domain adaptation methods to handle heterogeneous datasets, such as self-supervised learning [43], cross-domain adaptation [44], [45].…”
Section: Accepted Articlementioning
confidence: 99%
“…In knowledge transfer task (Task 3), simply fusing non-COVID-19 and COVID-19 dataset with the SOTA network could bias the model to learn more non-COVID-19 features. One can use more robust and powerful domain adaptation methods to handle heterogeneous datasets, such as self-supervised learning [43], cross-domain adaptation [44], [45].…”
Section: Accepted Articlementioning
confidence: 99%
“…MS-Net [9]: This work constructs a multi-site model that incorporates domain-specific auxiliary branches to improve the feature learning capacity and an online knowledge transfer strategy to explore the robust knowledge from multiple heterogeneous prostate MRI datasets for boosted segmentation.…”
Section: Table III the P-value With Paired T-test Of Our Methods With mentioning
confidence: 99%
“…Previous studies have revealed the limited improvement or even performance degradation of simple joint training at severe data heterogeneity [9], [32]. One crucial reason is that the BN layer in joint model will suffer from an inaccurate estimation of moving average values during the training phase due to the statistical difference across datasets (as shown in Fig.…”
Section: ) Separate Batch Normalization At Data Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations